(3KeQGJ GdChQGbs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s ((3eMeO Hf eMeO Hf CMeO GdMSfj GdMSjfj GdHNGQj Gdedc JLGQj Gdecj GdMfaj s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj acgfG HKeGQ ChQGb GdYdeGA aEfj hQjJ aj JSejI gPG GdcJGH HKeQGJ GdChQGb YGeG Cf bWhag de JOf dZjQ Phj GdCPhGb aef Pdc eG fbdJg ef OQI GdZhGU dCHj eMeO GdbGSe Hf Ydj GdMQjQj UGMH s
(3BNQgG (B:s
(3GfJgi eG acgJ Hg gfG ef KeQGJ GdChQGb, hGdUdGI hGdSdGe Ydj SjOfG eMeO QGcH GdHQGb, hYdi Bdg hCUMGHg hCRhGLg hCfUGQg hCJHGYg Edi jhe GdOjf hGdMeO ddg QH GdYGdejf s
(3hgh cJGH eTJed Ydi RHOI eG jMJGL (B"(3Edjg aj GdeLGdS hGdeMGad ef GdfhGOQ hGdMcGjGJs
(3HChdgG YTQ UaMGJ ajgG JbjjOGJ TYQjI hfKQjI hcPdc aj UaMI GdYfhGf JedjcGf CMOgeG SfI (B993(3g``s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
Keywords: (3GdCOHs